Effectiveness of digital feedback on patient experience and 30-day complications after screening colonoscopy: a randomized health services study - Bugajski, M.; Wieszczy, P.; Pisera, M.; Rupinski, M.; Hoff, G.; Huppertz-Hauss, G.; Regula, J.; Bretthauer, M.; Kaminski, M. F. (Endoscopy International Open, 2019)
Background and study aims European guidelines (ESGE) recommend measuring patient experience and 30-day complication rate after colonoscopy. We compared digital and paper-based feedback on patients’ experience and 30-day complications after screening colonoscopy.Patients and methods Screenees attending for primary screening colonoscopies in two centers from September 2015 to December 2016 were randomized (1:1) to an intervention arm (choice of feedback method) or control arm (routine paper-based feedback). Participants in the intervention arm could choose preferred feedback method (paper-based, automated telephone or online survey) and were contacted by automated telephone 30 days after colonoscopy to assess complications. Control group participants self-reported complications. Primary and secondary endpoints were response rates to feedback and complications questionnaire, respectively.Results There were 1,281 and 1,260 participants in the intervention and control arms, respectively. There was no significant difference in response rate between study groups (64.8 % vs 61.5 %; P = 0.08). Free choice of feedback improved response for participants identified as poor responders: younger than 60 years (60.8 % vs 54.7 %; P = 0.031), male (64.0 % vs 58.6 %; P = 0.045) and in small non-public center (56.2 % vs 42.5 %; P = 0.043).In the intervention arm, 1,168 participants (91.2 %) answered the phone call concerning complications. A total of 79 participants (6.2 %) reported complications, of which two (0.2 %) were verified by telephone as clinically relevant. No complications were self-reported in the control group.Conclusion The overall response rate was not significantly improved with digital feedback, yet the technology yielded significant improvement in participants defined as poor responders. Our study demonstrated feasibility and efficacy of digital patient feedback about complications after colonoscopy.